Depression, anxiety and stress among Swedish university students before and during six months of the COVID-19 pandemic: A cohort study. Issue 7 (November 2021) - Johansson, Fred; Côté, Pierre; Hogg-Johnson, Sheilah; Rudman, Ann; Holm, Lena w.; Grotle, Margreth; Jensen, Irene; Sundberg, Tobias; Edlund, klara; Skillgate, Eva
Aims: The COVID-19 pandemic has had a profound effect on societies and citizens worldwide, raising concerns about potential mental health impacts. We aimed to describe trajectories of depression, anxiety and stress symptoms during the COVID-19 outbreak compared to before the outbreak, and to determine if trajectories were modified by pre-pandemic loneliness, poor sleep quality and mental health problems. Methods: We conducted a cohort study with 1836 Swedish university students entering the study before 13 March 2020, the onset of the pandemic, with follow-ups within three (FU1) and six months (FU2) of the outbreak. Generalized Estimating Equations were used to estimate mean differences in symptom levels over time-periods, and to estimate potential effect modifications. Results: We found small differences in mean levels of the depression, anxiety and stress scale (DASS-21) over time. Compared to before the pandemic, depression increased by 0.25 points of 21 (95% CI: 0.04 to 0.45) at FU1 and decreased by 0.75/21 (95% CI:−0.97 to −0.53) at FU2. Anxiety decreased from baseline to FU1 by 0.09/21 (95% CI: −0.24 to 0.07) and by 0.77/21 (95% CI: −0.93 to −0.61) to FU2. Stress decreased from baseline to FU1 by 0.30/21 (95% CI: −0.52 to −0.09) and by 1.32/21 (95% CI: −1.55 to −1.09) to FU2. Students with pre-pandemic loneliness, poor sleep quality or pre-pandemic mental health problems did not have worse trajectories of mean mental health symptoms. Conclusions: Symptom levels were relatively stable during the first three months of the pandemic, while there was a slight decrease during the summer months, probably due to seasonality effects.